A new approach in Islamic education: mosque based teaching and learning - Ab. Halim Tamuri,; Muhamad Faiz Ismail,; Kamarul Azmi Jasmi, (Faculty of Education, UKM, Bangi, 2012)
Mosque plays an important role in education at the time of the Prophet Muhammad S.A.W and even before the British colonial period in Malaysia. Nowadays, the role of Islamic education has been taken over by schools and madrasa. Therefore, this article aims to discuss new approaches in teaching and learning of Islamic Education based on a mosque. The discussion focuses on the role of mosques in Islamic education in Malaysia and mosque based teaching and learning module. In addition, several research have shown that the mosque could contribute to the achievement of students in Islamic education subject. Thus, this innovation is seen to improve the role of mosque as an educational institution and form the collaboration between schools, mosques and the muslim communities in the implementation of Islamic Education.